Membangun Toleransi Beragama Melalui Kisah Nabi Ibrahim dalam QS. Maryam: 42−48 dan Relevansinya dalam Konteks Masyarakat Plural - Rohma, Dika Purnama Aulia (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
Religious tolerance is an important element in maintaining social harmony, especially in a plural society, such as Indonesia. Prophet Ibrahim's dialogue with his father in QS. Maryam: 42−48 is an example of religious tolerance. In these verses, Prophet Ibrahim shows the firmness of his faith, but still upholds a polite and respectful attitude towards his father, who has different beliefs. This paper aims to examine the values of religious tolerance shown through the dialogue of Prophet Ibrahim in these verses. This research is a library research using thematic interpretation method. The focus of the theme in this study is the value of religious tolerance in QS. Maryam: 42−48 which is then associated with the context of a plural society. From this analysis, there are three principles in building religious tolerance in a plural society, namely polite communication, respect for individual belief choices, and maintaining social relations despite different beliefs.